The Abrogation of Sale and Purchase Binding Agreement (PPJB) Deed of Notary That Contains Standard Clause by a Verdict - Lusiana Dwiyanti; Liza Prihandhini (Faculty of Law, Universitas Pekalongan, 2022)
The onus of making and undersign the Deed of Sale and Purchase Binding Agreement (PPJB) by a Notary is legally regulated in the PUPR Ministerial Decree No. 11/2019. This provides an obligation for a Notary in contrive the clause of the Binding Agreement that guarantees a legal preservation in the transition of land rights. In this research, the PPJB was using a standard clause containing an exoneration clause, thus causing an abrogation by a Verdict. This article uses a normative juridical research method, with secondary data and qualitative analysis. The eventuate is illustrate that the use of the principle of contract law is not legally valid if it contains an exoneration clause in it. As Public Officials who are charged with important duties and responsibilities, Notaries and PPATs must know all about legal studies related to make the deed so can avoid all lawsuits from parties that been disadvantaged due to disputes from the deed in the future.